The IN VIVO UTILIZATION OF ANTAGONISTIC INTERACTION ABILITIES OF BIOLOGICAL AGENTS AGAINST PATHOGENIC FUNGUS OF Fusarium spp. FOR CONTROL OF STEM ROT DISEASE IN THE FIG CUTTINGS (Ficus carica L) AND ITS EFFECT ON PLANT GROWTH: Tin, Trichoderma - hadi, pramono hadi; Masnur, Moh; Rachmawatie, Srie Juli (Universitas Islam Balitar, 2021)
ABSTRACT This study aims to determine the effectiveness of the inoculation of antagonistic biological agents in controlling stem rot disease caused by the pathogenic fungus Fusarium spp., and to increase the growth of fig stem cuttings (Ficus carica L.). This research was conducted at the Greenhouse of the Faculty of Agriculture, Islamic University of Batik Surakarta (UIBS), from September 2020 to December 2020. This study used a completely randomized design (CRD)., with 6 types of treatment, consisting of control, Trichoderma, Gliocladium, Corynebacterium, PGPR, and synthetic fungicide Mancozeb as a comparison, with 3 repetitions and 3 sub-repetitions. Observations consisted of several parameters, namely: disease incubation period, disease incidence, disease severity, shoot growth period, shoot height, leaf number, leaf area, root length, and number of roots. The results showed that Trichoderma treatment gave the best results for all observed parameters, even better than Mancozeb which is usually used by farmers. This is because Trichoderma has the ability of antagonistic in the form of very aggressive competition, producing antibiotic, and mycoparasitic mechanism against the pathogenic fungus Fusarium spp., so its utilization can be applied in organic farming to control stem rot disease which is more environmentally friendly. Trichoderma can also be used as biofertilizer because it has the ability as a good biodecomposer, its can breakdown nitrogen nutrients, dissolve phosphate, and provide micro nutrients, and even release the hormones auxin, cytokinins and ethylene, so that its effectiveness can stimulate and increase vegetative growth of fig plants in the form of shoots, leaves and roots. Keywords: fig, Fusarium spp., biological agent, Trichoderma, Mancozeb